2019
DOI: 10.1200/jco.19.00354
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccine Effectiveness Among Patients With Cancer: A Population-Based Study Using Health Administrative and Laboratory Testing Data From Ontario, Canada

Abstract: PURPOSE Seasonal influenza vaccination is recommended for patients with cancer despite concerns of disease or treatment-associated immunosuppression. The objective of this study was to evaluate vaccine effectiveness (VE) against laboratory-confirmed influenza for patients with cancer. PATIENTS AND METHODS We conducted an observational test-negative design study of previously diagnosed patients with cancer 18 years of age and older who underwent influenza testing during the 2010-2011 to 2015-2016 influenza seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…Our primary outcome combined influenza hospitalisations and deaths but was dominated by the former; it is plausible that there may be a lower threshold for hospitalisation in cancer survivors which could have exaggerated the difference in risk of the primary outcome between cancer survivors and controls, but is unlikely to fully explain the large associations we observed. Finally, we had some missing data on smoking and BMI data, and we excluded those with missing data from the analysis; this is unlikely to affect our findings under the Improving influenza vaccination coverage among cancer survivors should be a priority, as the vaccine is both effective and safe 29,30 but coverage has been reported in the range of 50% to 76% among cancer survivors in the US and in the UK. 31,32 Immunisation for streptococcus pneumoniae may also be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our primary outcome combined influenza hospitalisations and deaths but was dominated by the former; it is plausible that there may be a lower threshold for hospitalisation in cancer survivors which could have exaggerated the difference in risk of the primary outcome between cancer survivors and controls, but is unlikely to fully explain the large associations we observed. Finally, we had some missing data on smoking and BMI data, and we excluded those with missing data from the analysis; this is unlikely to affect our findings under the Improving influenza vaccination coverage among cancer survivors should be a priority, as the vaccine is both effective and safe 29,30 but coverage has been reported in the range of 50% to 76% among cancer survivors in the US and in the UK. 31,32 Immunisation for streptococcus pneumoniae may also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also have implications for preventive medicine in the coming autumn and winter, when influenza and SARS-CoV-2 are expected to coexist in the population. Improving influenza vaccination coverage among cancer survivors should be a priority, as the vaccine is both effective and safe 29,30 but coverage has been reported in the range of 50% to 76% among cancer survivors in the US and in the UK. 31,32 Immunisation for streptococcus pneumoniae may also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, virus eliminating immune response may be difficult to illicit in immunocompromised cancer patients. Vaccine effectiveness in general tends to be lower in patients with cancer, much lower for those with hematologic malignancies [75]. Utilization of long-term immune memory from convalescent individuals may provide alternate strategies for patients with hematological malignancies.…”
Section: Covid-19 and The Immune Responsementioning
confidence: 99%
“…All of these factors highlight the complexity and the steep learning curve in understanding thoroughly this process, as well as the challenges faced in answering questions related to the many possible scenarios. The efficacy of other types of vaccines in patients with cancer has been previously evaluated, with conflicting results: while some studies investigating influenza vaccines have previously shown substantial efficacy in cancer patients [ 23 , 24 ], others have shown decreased or nondurable immune responses [ 25 , 26 ]. This further highlights the heterogeneity and complexity of immune responses in this specific population.…”
Section: Safety and Efficacy Of Sars-cov-2 Vaccines In Cancer Patientsmentioning
confidence: 99%